Règlement des Congrès et du Bureau. Statuts de la Commission Interparlementaire = Geschäftsordnung für die Kongresse und für das Bureau. Satzungen der Interparlamentarischen Kommission = Regulations of the Congress and of the Bureau. Statutes of the Interparliamentary Commission. - Bureau Socialiste International; Internationales Sozialistisches Bureau; International Socialist Bureau (Bruxelles : Maison Du Peuple, 1912)
Bibliotheek Camille Huysmans
Adres: Camille Huysmans, Maison du Peuple, rue Joseph Stevens 17, Bruxelles
Frans
Duits
Engels
Brochure
Keywords: Socialistische Internationale; internationale arbeidersbewegingen